Analisis Kekuatan Dan Kelelahan Konstruksi Pondasi Mesin Kapal General Cargo 6088 GT - Nina Bonita; Adi Wirawan Husodo; Heroe Poernomo (Proceedings Conference on Marine Engineering and its Application, 2023)
A ship inspection outside the inspection schedule is called an additional inspection.The 6088 GT general cargo ship conducted an additional inspection because the mainengine failed to operate and replaced the wuxi antai power X8320ZC4B-1 engine weighing26700 kg with a yanmar 8N330-WU engine weighing 43000 kg. It is necessary to recalculatethe strength of the main engine foundation. Because the main engine foundation is thestructural support of all the loads above it including the engine itself. After the calculation ofstrength, it is necessary to calculate fatigue, after calculating the fatigue of the main enginefoundation, the estimated age of the engine foundation will be known so that the owner canschedule a replacement according to the ship's inspection schedule. In completing this FinalProject, the method used is the finite element method with input 3D modelling of thefoundation and its loading conditions in the Finite Element Method software. The results ofthe analysis can be seen from the load given of 421400 N with variations in the main engineat 100% rpm conditions and at service speed, the maximum stress obtained is 39.935 MPawith a permit stress value of 230 MPa, while the maximum deformation that occurs is 0,097mm with a permit deflection value of 12.300 mm. Then obtained a cycle value of 82129000,the estimated fatigue life of the main engine foundation is 25.65 years